Funções do desenho de arquitetura: argumentos para o ensino do projeto - Joana Barbosa Vieira da Silva (2021)
This dissertation examines the separation of architectural design from architectural construction. It is divided into two parts. The first one concerns a theoretical approach and addresses the role of drawing by following the tracks of Sérgio Ferro’s critique on separate design, providing new historical elements. The process of conception has been separated from construction since the Renaissance and drawing is analysed according to its function in constructive operations. The goal is to understand how architectural design got detached from the material operation to which it refers to, and began following the logic of the drawing instruments. The second part of the thesis concerns a pedagogical issue. The Architecture course of the University of Porto (FAUP) was a case study for observing the role of drawing in architectural education. This study is integrated into a broader panorama that starts from the foundation of teaching of drawing in Porto city. FAUP belongs to the tradition of architecture as a mental thing where the exercise of free hand drawing is cultivated specifically as a cognitive tool and a process of thinking. Thus, the thesis deals with architectural design observed in two broad areas. On the one hand, it observes the negative attributes established by the dissociation between conceiving-building. On the other hand, it observes the positive attributes arising from that separation: drawing transcended its role as merely an operative activity and once separated it could be speculative and become an instrument for thinking, an exercise of personal expression and a means to know the world. The thesis concludes by conceiving the emancipatory function of drawing. If drawing has been responsible for the distancing between architectural design and construction, it can also be the answer for reintegration.